Early Diagnosis Of Oral Leukoplakia As A Key Factor In The Prevention Of Malignant Transformation - Yusupjanova Munira Abdukhamid qizi (International Journal of Medical Science and Public Health Research, 2026)
Oral leukoplakia is recognized as the most common potentially malignant disorder of the oral cavity and remains a major concern in preventive dentistry and oral medicine. Despite its often asymptomatic nature, oral leukoplakia carries a significant risk of malignant transformation into oral squamous cell carcinoma, particularly when diagnosis is delayed or clinical monitoring is insufficient. Early diagnosis plays a decisive role in reducing this risk, enabling timely intervention, elimination of etiological factors, and appropriate clinical management. This paper explores the importance of early detection of oral leukoplakia as a preventive strategy against malignant transformation. Emphasis is placed on epidemiological relevance, etiological factors, clinical and histopathological characteristics, diagnostic approaches, and the prognostic value of early identification. The paper also discusses the role of dental practitioners in screening, patient education, and long-term follow-up. By integrating clinical vigilance with modern diagnostic tools, early diagnosis can significantly reduce morbidity and mortality associated with oral cancer. Strengthening early detection strategies is therefore essential for improving patient outcomes and advancing oral cancer prevention.